Management Guidance and Counseling in Senior High Schools in the Face of Globalization Era (Indonesian Journal of Counseling and Development, 2023)
Globalization has permeated all facets of life, including education. Education transcends national borders, facilitated by technological advancements and various methodologies. The era of globalization has both positive and negative impacts on students. Consequently, counselors must guide students towards global progress while preserving existing cultural values. The execution of guidance and counseling management must be technology-based and globally oriented. This has implications for the programs developed and the collaboration with all personnel implementing guidance and counseling in senior high schools. To conduct guidance and counseling management in line with the developments in the globalization era, the quality of human resources, or the competence of counselors, needs to be enhanced to be sensitive to opportunities and responsive to global challenges. The method employed is descriptive with a naturalistic qualitative approach, which reveals real events in natural conditions (natural settings). The instrument in this naturalistic qualitative research is the researcher himself, through self-evaluation regarding his understanding of qualitative methods, mastery of theory, insight into the field being researched, and readiness and provisions for fieldwork. The subjects in this research were five guidance and counseling teachers, the principal, and three students at State Senior High School 4 Sungai Penuh. The results of this research provide an overview of counseling management in schools and the competencies that counselors need to master to navigate the era of globalization